2019
DOI: 10.3389/fonc.2019.00430
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Predictive Biomarkers for Endometrial Malignancies: N-Acylethanolamines

Abstract: Objective: To identify new biochemical markers for endometrial cancer (EC). Recent evidence suggests that members of the endocannabinoid system ( N -acylethanolamines) that bind to and activate receptors that are dysregulated in EC are involved in this tumour's biology. These observations suggest increased N -acylethanolamine levels in the tissue that might appear in plasma and could be used as disease biomarkers. Methods: N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…The expression of CB1R, AEA and palmitoylethanolamine lipid (PEA) were not significantly different between normal and tumour tissue although AEA and PEA showed elevated levels in EMC [76]. Statistical significance was reached in the study by Ayakanny et al who demonstrated that plasma and tissue AEA and PEA levels were significantly higher in EMC than in controls [78]. Since their levels are significantly higher in plasma of EMC patients than in the healthy controls, these biomarkers can be useful in early and non-invasive diagnosis of endometrial cancer.…”
Section: Endometrial Cancer (Emc)mentioning
confidence: 95%
“…The expression of CB1R, AEA and palmitoylethanolamine lipid (PEA) were not significantly different between normal and tumour tissue although AEA and PEA showed elevated levels in EMC [76]. Statistical significance was reached in the study by Ayakanny et al who demonstrated that plasma and tissue AEA and PEA levels were significantly higher in EMC than in controls [78]. Since their levels are significantly higher in plasma of EMC patients than in the healthy controls, these biomarkers can be useful in early and non-invasive diagnosis of endometrial cancer.…”
Section: Endometrial Cancer (Emc)mentioning
confidence: 95%
“…atrophic controls; FAAH was decreased whilst NAPE-PLD was increased. Since these metabolizing enzymes are responsible for controlling "steady state" levels of the NAEs, particularly AEA (17), they could be responsible for the increased AEA and PEA levels we previously reported for EC tissues (1). The lack of correlation between plasma NAE concentrations and lymphocytic FAAH activity in all the tumor grades (Figure 1), suggest that a concomitant loss of FAAH expression and an increase in NAPE-PLD expression in the endometrium is a possible reason for the observed higher levels of these NAEs in endometrial cancer, especially Type 1 EC.…”
Section: Discussionmentioning
confidence: 90%
“…We therefore, examined the possibility that protein expression does not exactly mirror the pattern of transcript expression and found that this indeed was the case for NAPE-PLD here, where the transcripts were not significantly higher in EC, but the protein levels were. These data suggest that only FAAH expression is likely to be involved in the modulation of tissue AEA, OEA and PEA levels in EC (1). We could have used immunoblotting techniques to complement the transcript experiments, but immunoblotting techniques do not indicate where a protein is synthesized or might act.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations